Ethical Quagmires for Government Lawyers: Lessons for Legal Education - Susan Saab Fortney (Washington University Journal of Law and Policy, 2022)
Each presidential administration faces its own challenges related to the ethics of government officials and lawyers. What distinguished the Trump presidency was the steady stream of news reports that related to controversies involving government lawyers. In examining various controversies, this Essay argues that the ethical standards applicable to government lawyers are often thorny and debatable. Fortney discusses how controversies involving alleged misconduct by government lawyers reveal the range and complexity of ethical dilemmas that government lawyers encounter. This Essay asserts that legal educators should do more to empower government lawyers to deal with such ethics issues. To highlight key ethics questions government lawyers must address, the author examines some of the most common and perplexing ethics issues that arise in government practice. Rather than simply criticizing the lawyers involved in those controversies, the conclusion suggests a positive outcome of the Trump era is for legal educators to take seriously ethics issues encountered by government lawyers and spend more time on them in the classroom. By doing so, legal ethics professors discharge their own professional responsibility to their students and future public servants.
Keywords: President; Administration; Ethics; Government; Officials; Lawyers; Trump; Controversies; Government lawyers; Ethical; Standards; Perplexing; Misconduct; Dilemmas; Legal education; Educators; Legal; Professional; Responsibility; Public servants; Students